Percipience of leadership characteristics in identifying emergent leader - Reynaldo V. Ruga; Emelyn R. Villanueva; Emelia B. Ramos (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study examined the leadership characteristics associated with emergent leaders and explored how these characteristics are perceived by administrators and faculty members within an academic context. Guided by a convergent parallel mixed-methods approach, data were gathered from 189 respondents drawn from nine satellite campuses of a state university, comprising 54 administrators and 135 faculty members. Quantitative data were collected using a structured survey questionnaire measuring percipience across leadership domains, while qualitative data were obtained through written narrative reflections. Descriptive statistics and independent samples t-tests were employed to determine levels of percipience and significant differences between groups, and thematic analysis was used to analyze qualitative narratives. The study aimed to describe leadership traits expressed through participants’ accounts, determine the level of percipience across key leadership domains, compare perceptions between administrators and faculty members, and identify significant differences in their assessments. Findings revealed that emergent leadership is recognized through consistent ethical conduct, effective communication, relational engagement, and adaptive decision-making rather than formal position alone. Although both groups shared similar views on core leadership attributes, variations emerged in the emphasis placed on delegation, adaptability, and change-oriented behaviors, reflecting differences in professional roles and responsibilities. Integrating quantitative and qualitative findings, the study developed the LEADWISE integrated leadership framework, which explains leadership emergence as a dynamic and relational process shaped by leader-ship traits, wisdom, integrity, social engagement, and ethical awareness. The study contributes to leadership research by offering an empirically grounded framework that supports leadership identification and development in complex organizational settings, particularly within higher education institutions.